If I'm found [compact disc, unabridged] - Blackstock, Terri, 1957- (Blackstock, Terri, 1957- If I run series, 2017)
Casey doesn't know why Dylan let her escape just as the police were closing in, but she knows she's got to hide again. New name, new look, new city, new job. But hiding isn't enough. Somehow, she's got to bring Brent's killer to justice. Can she gather enough evidence without getting caught? And even though she wants to trust Dylan, can she really?